Social well-being and transformative service research: evidence from China. Issue 6 (19th July 2019) - Feng, Kuo; Altinay, Levent; Olya, Hossein
Abstract : Purpose: This empirical study aims to investigate the influence of socially supportive services provided by commercial senior living services on older customers' social well-being. This study seeks to test the moderating role of social connectedness on the above associations. It explores necessary conditions and causal recipes from the combination of interactions and social connectedness to predict customers' social well-being. Design/methodology/approach: Data were collected from 190 older customers residing in commercial senior living services in Beijing, Shanghai and Shenyang in China. The proposed structural and configurational models were tested using structural equation modelling and fuzzy-set qualitative comparative analysis (fsQCA). Findings: The results of the model testing illustrate that peers have no influence on the social well-being of older customers. However, positive interactions with employees and outsiders are supportive resources that increase older customers' social well-being. Social connectedness moderates the relationship between interaction with peers and the social well-being of customers. fsQCA results revealed that complex combinations of interactions and social connectedness predict social well-being. Interactions with employees, peers and outsiders appeared as necessary conditions to achieve social well-being. Originality/value: This study provides evidence for how commercial senior living services can serve as a space to exchange socially supportive resources with employees and outsiders, which enhance older customers' social well-being.